ACO/ARO/AIO-21 - Capecitabine-based chemoradiotherapy in combination with the IL-1 receptor antagonist anakinra for rectal cancer Patients: A phase I trial of the German rectal cancer study group - Fleischmann, Maximilian; Diefenhardt, Markus; Nicolas, Adele M.; Rödel, Franz; Ghadimi, Michael; Hofheinz, Ralf-Dieter; Greten, Florian R.; Rödel, Claus; Fokas, Emmanouil (Clinical and translational radiation oncology, 2022)
•Response to chemoradiotherapy in rectal cancer is highly heterogeneous, ranging from complete response to tumor progression.•Interleukin-1 signaling polarizes cancer-associated fibroblasts (CAF) towards an inflammatory phenotype and predisposes iCAFs to irradiation-induced senescence.•Targeting interleukin-1 could potentially reconstitute the tumor microenvironment and improve therapy response.•The ACO/ARO-AIO-21 phase I trial is testing the interleukin-1 receptor antagonist anakinra in combination with fluoropyrimidine-based chemoradiotherapy in rectal cancer. Recent advances in the treatment algorithm of locally advanced rectal cancer (LARC) have significantly improved complete response (CR) rates and disease-free survival (DFS), but therapy resistance, with its substantial impact on outcomes and survival, remains a major challenge. Our group has recently unraveled a critical role of interleukin-1α (IL-1α) signaling in activating inflammatory cancer-associated fibroblasts (iCAFs) and mediating radiation-induced senescence, extracellular matrix (ECM) accumulation, and ultimately therapy resistance. We here summarize the recently initiated ACO/ARO/AIO-21 phase I trial, testing the IL-1 receptor antagonist (IL-1 RA) anakinra in combination with fluoropyrimidine-based chemoradiotherapy (CRT) for advanced rectal cancer. The ACO/ARO/AIO-21 is an investigator-driven, prospective, open-labeled phase I drug-repurposing trial assessing the maximum tolerated dose (MTD) of capecitabine administered concurrently to standard preoperative radiotherapy (45 Gy in 25 fractions followed by 9 Gy boost in 5 fractions) in combination with fixed doses of the IL-1RA anakinra (100 mg, days −10 to 40). Capecitabine will be administered using a 3 + 3 dose-escalation design (500 mg/m2 bid; 650 mg/m2 bid; 825 mg/m2 bid, respectively) from day 1 to day 40. Response assessment including digital rectal examination (DRE), endoscopy and pelvic magnetic resonance imaging (MRI) is scheduled 10 weeks after completion of CRT. For patients achieving clinical complete response (cCR), primary non-operative management is provided. In case of non-cCR immediate total mesorectal excision (TME) will be performed. Primary endpoint of this phase I trial is the MTD of capecitabine. Based on extensive preclinical research, the ACO/ARO/AIO-21 phase I trial will assess whether the IL-1RA anakinra can be safely combined with fluoropyrimidine-based CRT in rectal cancer. It will further explore the potential of IL-1 inhibition to overcome therapy resistance and improve response rates. A comprehensive translational research program will expand our understanding from a clinical perspective and may help translate the results into a randomized phase II trial.